Electromyography in front crawl technique - case study - Conceicao, A.; Silva, A.; Palma, A.; Silva H.; Gamboa, H.; Louro, H. (The Open Sports Sciences Journal, 2010)
The need to develop systems electromyographic (EMG) in the aquatic environment, has led several researchers to refine these instruments to ensure the credibility of the data provided by EMG. The aim of this study is to characterize the behavior of two muscle muscles involved in the crawl technique (biceps brachii and triceps brachii) over a test of 200m crawl. 1 male swimmer trained was subjected to a test consisting of a maximum voluntary contraction (MVC) of the Biceps Brachii (BB) and Triceps Brachii (TB) for standardization. A protocol of 4 x 50m with an interval of 15 seconds at a swimming speed of pre-established, making each part to 95% of transit time for 200m crawl.